Assessing the ecosystem services supplied by freshwater flows in Mediterranean agroecosystems (Agricultural Water Management, 2012)
Water performs essential ecological functions in agroecosystems and supplies an array of hydrologic ecosystem services (HES). The nature and quantity of HES is intimately linked with the management of the territory, and the capacity of the different land uses to partition rainfall into green (evapotranspiration) and blue (runoff) freshwater ﬂows. This paper presents an innovative method to empirically assess the underlying relationship between the use and management of Mediterranean agroecosystems, their spatial pattern of green and blue freshwater ﬂow generation and the provision of HES. We test this approach in Sierra Norte de Sevilla, a characteristic Spanish agro-forestry system. To assess the hydrological functioning we used the spatially explicit hydrologic model BalanceMED. HES’ identiﬁ- cation and societal valuation was done through an expert panel. The hydrologic performance and the social values ascribed to the different services were combined to identify key provisioning areas or HES hotspots. Our results show that multifunctional agroecosystems, where agrarian and forestry activities co-exist, optimize the partition and use of freshwater ﬂows and supply the largest bundles of HES at a wide range of spatial scales. The often low proﬁtability of these extensive activities is prompting either the intensiﬁcation or the abandonment of many Mediterranean agro ecosystems. We discuss the trade-offs in HES associated with these land use trends, and we illustrate the potential options available for implementing payments for ecosystem services (PES) schemes to pursue “win–win” management solutions.